2014
DOI: 10.1021/jp508141q
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Catalytic Steps on Extra-Framework Metal Centers in Zeolites. A Case Study on Ethylene Dimerization

Abstract: In a case study of organometallic catalytic reactions, this work benchmarks density functional theory calculations on zeolite-supported transition metal complexes. Elementary steps of ethylene dimerization and hydrogenation reactions involving the complex [Rh(C2H4)2(H2)]+, supported on faujasite, were examined by comparing explicit QM (quantum mechanics) cluster models as well as QM/MM (molecular mechanics) embedded models to plane-wave periodic models as reference. Two QM cluster models, 1T and 5T where T ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 75 publications
0
31
0
Order By: Relevance
“…The QM region includes on average 54 atoms, excluding hydrogen atoms used to terminate the Si atoms. The QM regions used here are larger than used in previous work [11,[32][33][34][35] and we found it to be more than sufficient for the calculations to converge (Figure S4). Finally, for the calculations of NO adsorption in Pd-CHA, the number of QM atoms was extended as needed to account for potential interactions of NO with other Si/O atoms in the framework.…”
Section: Selection Of the Qm And MM Regionsmentioning
confidence: 83%
“…The QM region includes on average 54 atoms, excluding hydrogen atoms used to terminate the Si atoms. The QM regions used here are larger than used in previous work [11,[32][33][34][35] and we found it to be more than sufficient for the calculations to converge (Figure S4). Finally, for the calculations of NO adsorption in Pd-CHA, the number of QM atoms was extended as needed to account for potential interactions of NO with other Si/O atoms in the framework.…”
Section: Selection Of the Qm And MM Regionsmentioning
confidence: 83%
“…In the same spirit, we used an 83T cluster, [22] taken from the zeolite lattice, to model the ethene conversion activity at a Ir(I) center anchored in FAU. This cluster model comprises a supercage unit with additional sodalite cages and hexagonal prisms, with 278 atoms in total, Figure S1a of the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…Within this 83T cluster, we used a QM partition of 5T centers which contains the AlO 4 moiety carrying the metal complex, surrounded by 4 neighboring Si units, Figure S1b of the Supporting Information. This hybrid QM/MM 5/83T model was treated with the ONIOM approach, [23] a strategy which was reported [22] to be equally well‐suited as periodic models for describing the catalytic reactions addressed in the present study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reverse hydrogen spillover reactions on Rh 6 and other late‐transition metal clusters supported by zeolites have been studied in detail . Benchmark studies of QM/MM calculations have been reported for C–C coupling and hydrogenation reactions involving zeolite‐supported [Rh(C 2 H 4 ) 2 (H 2 )] + . Structure and properties of protonated Rh n clusters in Y‐zeolite were also investigated using periodic DFT …”
Section: Introductionmentioning
confidence: 99%